PELATIHAN DIGITAL MARKETING UNTUK MENINGKATKAN KINERJA PELAYANAN HAPUS TATO PRO CARE - Fachruddin Edi Nugroho Saputro; Adika Sri Widagdo; Ardiansyah; Habib Ismail; Krisna Nuresa Qodri; Nisrina Akbar Rizky Putri (Jurnal Abdimas Universitas Insan Pembangunan Indonesia, 2024)
Promotion is an activity that aims to inform, influence, and influence consumer attitudesand behavior so that they are interested in and buy the products or services offered. In itsapplication, promotion has many methods including direct promotion or calledconventional promotion. Conventional promotion refers to promotion methods orstrategies that have long been used before the digital era or have not utilized informationtechnology. Promotion by utilizing information technology also known as digital marketingis an innovation in the marketing process promotional activities that involve the use oftechnology and digital platforms to achieve marketing goals to expand and enhancetraditional marketing functions.‘Hapus Tato Pro Care’ have constraints that have notmaximized the use of information technology in the promotion of tattoo removal servicesand the limited reach of targeting in the promotion of tattoo removal services. Byconducting training and being guided in creating content that will be used as promotionalmedia. In addition, participants will be guided to create captions and keywords used onsocial media to attract the attention of other social media users, participants gain skills inmanaging social media and doing graphic design better.